Kelimpahan Populasi dan Kondisi Habitat Labi-Labi (Dogania subplana: Reptilia: Trionychidae) di Kawasan Kampus Universitas Andalas Padang - Bimo Premono; Rizaldi Rizaldi; Izmiarti Izmiarti (Jurnal Biologi Universitas Andalas, 2015)
A study on population and habitat of forest softshelled turtle (Dogania subplana: Reptilia: Trionychidae) has been conducted from January to March 2014. This study aimed to understand population abundance and to describe non-natural and natural habitats. Population abundances were found out through searching, counting and release methods. Habitats were described based on physic-chemical, potential food-resource and vegetation factors. The turtles were more abundance in non-natural habitat (33 individual of 640 m²) than natural habitat (5 individual of 5.100 m²). The turtles were abundance in sand and gravel streams of non-natural habitat and sand and rocky streams of natural habitat. The turtles prefered in slow streams (0-10 cm/s) and neutral pH (7.1-7.6).Keywords: population abundance, non-natural habitat, natural habitat, Dogania subplana.